Pengembangan Bahan ajar Berbasis Word Square Untuk Meningkatkan Hasil Belajar Tematik - Fauziana, Fauziana; Dewi Saputri, Rikei; Zulaiha, Siti; Riyan Oktori, Agus (PGMI IAIN Lhokseumawe, 2023)
Teaching materials based on Word Square are instructional modules designed as a game to enhance students' abilities in answering questions and finding suitable answers within answer squares. This game encourages students to be more careful, independent, and meticulous. The aim of this research is to assess the development, feasibility, and effectiveness of Word Square teaching materials in improving thematic learning outcomes for third-grade students at SDN 4 Rejang Lebong. The study adopts the Research and Development (R&D) approach, following the Borg and Gall research procedure, encompassing potential problems, data collection, product design, design validation, design revision, product testing, product revision, and usage testing. The research employs pre-test and post-test assessments with the same group to gauge children's understanding of using Word Square teaching materials. The analysis reveals that teachers express an 88.64% need, categorized as